Music listening for psychological well-being in adults with acquired vision impairment: a feasibility randomised controlled trial - Somani, Nurbanu; Street, Alexander; Beukes, Eldre Wiida; Zhang, Jufen; Allen, Peter M. (Frontiers in Psychiatry, 2025)
PurposeVision impairment (VI) has a profound impact on mental health and well-being. Music-based interventions, such as active music listening, have potential to induce relaxation, improve mood, and reduce stress. This study investigated the feasibility and acceptability of a supportive self-care music intervention in adults with acquired VI, who ran their listening program independently.MethodsA two-arm, parallel-group, single-blind feasibility randomised controlled trial compared: (1) daily music listening with brief mindfulness instructions and (2) daily music listening alone. The study adhered to the CONSORT extension for pilot and feasibility trials and the music reporting checklist. Feasibility was determined by collecting data on attrition, through recruitment and retention at pre-post and 3-month follow-up, including adherence and fidelity which were determined by participants’ questionnaire and daily log completion, respectively. Acceptability was determined through data capture in the questionnaires. To assess whether the music intervention had an impact on anxiety and depression and stress, the Hospital Anxiety Depression Scale (HADS) and the Perceived Stress Scale (PSS-14) were used.ResultsEighty-one VI participants were randomised to mindful music listening (n = 41) or music listening alone (n = 40), with 85% (n = 69) completing the intervention (post intervention end-point). A rating of ‘highly satisfied’ was given for the intervention by 77% (n = 53) of participants. Feasibility was determined through retention which was 71% at the three-month follow-up, and adherence to the daily log completion, which was low (16%), resulting in insufficient data to assess fidelity to the music listening. HADS and PSS-14 data indicated a reduction in anxiety, depression and stress at post-intervention phase.ConclusionsThe recruitment and retention rates suggest that an efficacy study is feasible. However, adherence to daily log completion was low, resulting in uncertainty regarding the fidelity of the listening conditions. While completing the daily logs was not required in this study, it should be mandatory in future trials.Clinical Trial Registrationhttps://clinicaltrials.gov/study/, identifier NCT05243732.